Do Economic Depressions Contribute to CO2 Emissions? An ARDL Bound Approach - Karim, Norzitah Abdul; Senawi, Azhan Rashid; Muhamat , Amirul Afif; Nizar, Nurhuda; Wahab, Norazlina Abd; Ab Kadir , Musaab (International Journal of Energy Economics and Policy, 2023)
Total carbon dioxide (CO2) emissions are undoubtedly emitted to the environment, humans, ecosystems, and global economic growth. However, less research has examined the effect of economic depression on carbon dioxide emission (CO2), especially in Malaysia. Thus, this study intents to examine the impact of the macroeconomic problems, namely unemployment (UNEMP) and the growing number of people: population (POP), on the CO2 emissions in Malaysia. The study analyzes the data for 28 years, covering the period of 1991–2019, employing a bound ARDL model as an estimation method. The time series data were sourced from the World Bank Development Indicators database. The finding from the study shows that CO2 emissions, POP, and UNEMP have a long-term cointegration. Under this situation, all variables indicated; UNEMP and POP lead to environmental degradation in Malaysia in the long run. The impact of both UNEMP and POP on CO2 emissions is positive. Moreover, it is also found that the damage of economic depression will take only around one year and a month on CO2 emissions. Thus, based on this novel finding, a comprehensive set of economic policies is required to ensure our economy is in good condition and hence suggested for maintaining the environmental quality.